A novel oral rabies vaccine enhances the immunogenicity through increasing dendritic cells activation and germinal center formation by expressing U-OMP19 in a mouse model. Issue 1 (1st January 2021) - Zhao, Jianqing; Zhang, Yijing; Chen, Yixi; Zhang, Juntao; Pei, Jie; Cui, Min; Fu, Zhen F.; Zhao, Ling; Zhou, Ming
ABSTRACT: Rabies remains a public health threat in most parts of the world. Dogs, especially stray dogs, are the main sources of rabies transmission in developing countries, while wild animals are primarily responsible for the spread of rabies in developed countries and play an emerging role in rabies transmission in developing countries. Oral vaccination is the most practical method for rabies control in these animals, and the greatest challenge for oral vaccination is the hostile environment and large quantity of proteases in the gastrointestinal tract. In the present study, a promising adjuvant with potential protease inhibitory activity, unlipidated outer membrane protein 19 (U-OMP19), was inserted into the genome of the recombinant rabies virus (rRABV) strain LBNSE, designated LBNSE-U-OMP19, and the immunogenicity of LBNSE-U-OMP19 was investigated. LBNSE-U-OMP19 could potentially protect viral glycoprotein from digestion by gastrointestinal fluids in vitro . The expression of U-OMP19 attenuated viral pathogenicity by restricting viral replication in the central nervous system (CNS) and repressing the production of inflammatory chemokines and cytokines. After oral vaccination, LBNSE-U-OMP19 recruited dendritic cells (DCs), follicular helper T (TFH ) cells and germinal center (GC) B cells, promoted the formation of GCs, and increased the population of plasma cells in immunized mice, resulting in higher levels of RABV-neutralizing antibodies and better protection in mice immunized with LBNSE-U-OMP19 than in those immunized with the parent virus LBNSE. Together, our data suggest that LBNSE-U-OMP19 is a promising candidate for oral rabies vaccines.